Humanização e sensibilidade: educação e uso do corpo em Giorgio Agamben - Marcelino, Patrícia (2019)
The purpose of this thesis, linked to the Education Fundamentals line of the Graduate Program in Education of the University of Passo Fundo (UPF / RS), is to develop a proposition of education of the human body that differentiates the historically developed formation about it as an instrumentalizer, performative, utilitarian and functional. It was proposed the development of an education of the sensitive sustained in the idea of a new form of human being in which the body is not understood as an object of appropriation and productivity, but of use and conscious care. Supported by Giorgio Agamben, especially on the concepts of body use, naked life, inoperability and profanity, and by authors who connect him with education, a conception of humanizing, conscious and sensitive education was presented, pointing out that the human relationship with corporeality cannot be determined either by natural instrumentality or by the established political order, but rather by an attitude of contemplation and inoperability as a new form of life.The general objective was to identify Agambenian contributions and connections with education and the use of the body from the perspective of inoperability and as a possibility to experience it in a more tender, sensitive, human way. Foucault, fundamental to the constitution of Agamben's thought, especially with regard to the concept of biopolitics, the main link between the two authors. Fundamentally, the notion of corporeality as an instrument of production in the process of capitalist globalization was problematized, clarifying the concept of the use of the body as a source of emancipation and humanization. To this end, a bibliographic study was developed, with a reconstructive-critical-hermeneutic methodological approach to education. The analysis focused on the idea of replacing the conception of education as 'action' with the conception of education as 'use of bodies', pointing out that this is a challenging but effective approach to humanization and the development of greater sensitivity towards human body and life in general. By way of conclusion, it is considered that Agamben's analytical categories may contribute to the resignification of body education. This is possible using the Agambenan devices of profanity and inoperability as a way of life, turning them into a critical and transformative experience, taking another look at the education of corporeality in order to make the use of the body a more practical humanized, loving, tender and sensitive.